Eduwisata sebagai Model pengembangan Wisata yang Berorientasi pada Pendidikan dan Kesadaran lingkungan di Hutan Mangrove Karangsong Indramayu-Indonesia - Sudirman, Sudirman; Rahayuningsi, Margareta; Marianti, Aditya (Jurnal SOLMA, 2024)
Background: Mangrove forests are very important coastal ecosystems because they provide various benefits, including providing shelter for various biological species, protecting beaches from abrasion, and storing carbon. The potential of the Karangsong mangrove forest, which is an integrated area, is very important for tourism growth, especially sustainable natural tourism. This potential also functions as a means to improve education and environmental preservation, as well as as an economic resource. An approach that may be effective is to integrate education and tourism, or what is known as "edutourism", into mangrove forest conservation and development efforts. This research aims to examine the potential of natural resources and human resources in the Karansong mangrove forest area to support edutourism as a tourism development model oriented towards education and environmental awareness in the Karangsong mangrove forest. Methods: Research methods include surveys, interviews, literature studies, and comparative analysis. Result: the edutourism model in the Karangsong mangrove forest provides opportunities for visitors, especially students, to learn about ecology, biodiversity, and the importance of protecting the environment, especially the mangrove ecosystem. Conclusion: Providing economic opportunities for local communities, such as through sales of local products, local tour guides, or other activities related to tourism.